Private Interaction Between Firm Management and Sell‐Side Analysts - SOLTES, EUGENE (Journal of Accounting Research, 2014)
ABSTRACT Although sell‐side analysts often privately interact with managers of publicly traded firms, the private nature of this contact has historically obscured direction examination. By examining a set of proprietary records compiled by a large‐cap NYSE‐traded firm, I offer insights into which analysts privately meet with management, when analysts privately interact with management, and why these interactions occur. I also compare private interaction to public interaction between analysts and managers on conference calls. The evidence suggests that private interaction with management is an important communication channel for analysts for reasons other than firm‐specific forecasting news.